Electrochemical device and electrical equipment containing the same

By using specific positive electrode active materials in the positive electrode sheet of lithium-ion battery and adjusting relevant parameters to control the exothermic peak characteristics, the shortcomings of lithium-ion batteries in the cycle performance, rate performance and safety performance are solved, and higher thermal stability and battery performance are achieved.

CN115176370BActive Publication Date: 2025-04-08NINGDE AMPEREX TECHNOLOGY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180013610.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-28
Publication Date
2025-04-08
Estimated Expiration
2041-09-28

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have shortcomings in circulation performance, rate performance and safety performance, and are difficult to meet the high market requirements for energy density, safety and service life.

Method used

By using a specific positive electrode active material in the positive electrode sheet, and by adjusting the liquid injection coefficient, the upper limit voltage after packaging, the melting temperature and the melting stand-alone time, the exothermic peak characteristics of the DSC curve of the positive electrode sheet between 150°C and 400°C, the peak position difference between the first exothermic peak A1 and the second exothermic peak A2 is between 20°C and 150°C, ensuring the thermal stability of the interface protective film and the positive electrode active material.

Benefits of technology

It improves the circulation performance, rate performance and safety performance of the electrochemical device, ensures the stability of the protective film on the surface of the positive electrode active material, inhibits side reactions, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005291512030000021
    Figure FDA0005291512030000021
  • Figure FDA0005291512030000022
    Figure FDA0005291512030000022
  • Figure GDA0005291512040000041
    Figure GDA0005291512040000041
Patent Text Reader

Abstract

Provided are an electrochemical device and an electrical equipment including the electrochemical device, wherein the electrochemical device comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode active material, and when the state of charge SOC of the electrochemical device is 90% to 100%, the DSC curve of the positive electrode sheet has a first exothermic peak A1 and a second exothermic peak A2 between 150°C and 400°C, wherein, based on the mass of the positive electrode active material, the first exothermic peak A1 is an exothermic peak with a peak intensity greater than 0.1 mW / mg closest to 400°C, the second exothermic peak A2 is an exothermic peak with a peak intensity greater than 0.1 mW / mg closest to 150°C, and the difference between the peak position Ta of the first exothermic peak A1 and the peak position Tb of the second exothermic peak A2 is 20°C to 150°C. The electrochemical device has good cycle performance, rate performance and safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemistry, and in particular to an electrochemical device and an electrical equipment comprising the electrochemical device. Background Art

[0002] Lithium-ion batteries have the advantages of high energy storage density, high open circuit voltage, low self-discharge rate, long cycle life, and good safety performance. They are widely used in various fields such as power storage, mobile electronic devices, electric vehicles, electric bicycles, and aerospace equipment. As mobile electronic devices and electric vehicles enter a stage of rapid development, the market has put forward higher and higher requirements on the energy density, safety performance, cycle performance, and service life of lithium-ion batteries. Summary of the invention

[0003] The purpose of the present application is to provide an electrochemical device and an electrical equipment comprising the electrochemical device, so as to improve the cycle performance, rate performance and safety performance of the electrochemical device.

[0004] The first aspect of the present application provides an electrochemical device, which includes a positive electrode sheet, and the positive electrode sheet includes a positive electrode active material. When the state of charge SOC of the electrochemical device is 90% to 100%, the DSC (differential scanning calorimetry) curve of the positive electrode sheet has a first exothermic peak A1 and a second exothermic peak A2 between 150°C and 400°C. Wherein, based on the mass of the positive electrode active material, the first exothermic peak A1 is an exothermic peak with a peak intensity greater than 0.1mW / mg closest to 400°C, and the second exothermic peak A2 is an exothermic peak with a peak intensity greater than 0.1mW / mg closest to 150°C, and the difference between the peak position Ta of the first exothermic peak A1 and the peak position Tb of the second exothermic peak A2 is 20°C to 150°C. It can be understood that the above-mentioned exothermic peaks include the exothermic peaks formed by the joint action of the interface protection film and the positive electrode active material itself, that is, the peak position Ta and peak intensity of the first exothermic peak A1, and the peak position Tb and peak intensity of the second exothermic peak A2 are jointly determined by the interface protection film and the positive electrode active material. Without being limited to any theory, based on the mass of the positive electrode active material, the peak strength of the second exothermic peak A2 is greater than 0.1mW / mg, and the difference between the peak position Ta of the first exothermic peak A1 closest to 400°C and the peak position Tb of the second exothermic peak A2 closest to 150°C in the exothermic peak is 20°C to 150°C, indicating that the peak position difference between the exothermic peaks formed by the interaction of the interface protective film and the positive electrode active material is small, and the interface thermal stability between the positive electrode active material and the electrolyte is high and not easily destroyed at high temperatures, thereby better protecting the surface of the positive electrode active material, inhibiting the occurrence of side reactions, and improving the stability of the positive electrode active material; at the same time, based on the mass of the positive electrode active material, the peak strength of the second exothermic peak A2 is greater than 0.1mW / mg, ensuring that there is sufficient protective film on the surface of the positive electrode active material. As a result, the thermal stability of the electrochemical device is effectively improved, so that the electrochemical device has good cycle performance, rate performance and safety performance.

[0005] In the present application, when the positive electrode sheet uses the same positive electrode active material, the injection coefficient, the formation upper limit voltage after the electrochemical device is packaged, the formation temperature, the formation standing time, etc. can be regulated so that the peak position, peak intensity, and the difference between the peak position Ta of the first exothermic peak A1 and the peak position Tb of the second exothermic peak A2 are controlled within the scope of the present application to achieve the purpose of the present application, so that the electrochemical device has good cycle performance, rate performance and safety performance. The present application does not particularly limit the specific range of the injection coefficient, the formation upper limit voltage after the electrochemical device is packaged, the formation temperature, and the formation standing time, as long as the purpose of the present application can be achieved.

[0006] In one embodiment of the present application, the peak position Ta of the first exothermic peak A1 is located at 250° C. to 400° C., and the peak position Tb of the second exothermic peak A2 is located at 200° C. to 300° C. In this way, the peak positions of the first exothermic peak A1 and the second exothermic peak A2 are both relatively high, thereby improving the thermal stability of the positive electrode active material and its surface protective film.

[0007] In one embodiment of the present application, the ratio S of the peak intensity of the first exothermic peak A1 to the peak intensity of the second exothermic peak A2 is 0.1 to 10. For example, the ratio S of the peak intensity of the first exothermic peak A1 to the peak intensity of the second exothermic peak A2 can be 0.1, 0.7, 1.2, 1.4, 1.5, 6.1, 9.8, 10 or any value between any two of the above numerical ranges. Further, the ratio S of the peak intensity of the first exothermic peak A1 to the peak intensity of the second exothermic peak A2 is 0.7 to 10. Without being limited to any theory, controlling the ratio S of the peak intensity of the first exothermic peak A1 to the peak intensity of the second exothermic peak A2 within the above range can reduce the stability difference between the positive electrode active material and its surface protection film, which is more conducive to improving the cycle performance and rate performance of the electrochemical device.

[0008] In one embodiment of the present application, after the positive electrode sheet is soaked in N-methylpyrrolidone (NMP) at 25°C for 8 hours, the N-methylpyrrolidone is replaced in the same ratio, and after repeated soaking twice, the DSC curve of the positive electrode sheet has an exothermic peak B between 240°C and 400°C, and the peak area of ​​the exothermic peak B is less than 360J / g based on the mass of the positive electrode active material; each time the positive electrode sheet is soaked in NMP, the volume ratio of the positive electrode sheet to NMP is 1:10 to 1:20. After the positive electrode sheet is repeatedly soaked in NMP three times, the protective film on the surface of the positive electrode active material has been mostly or completely washed away, so the peak position Tc of the exothermic peak B is mainly determined by the positive electrode active material. The peak position Tc of the exothermic peak B is located at 240°C to 400°C, and based on the mass of the positive electrode active material, the peak area of ​​the exothermic peak B is less than 360 J / g, indicating that the positive electrode active material has good thermal stability. In this way, the electrochemical device has good thermal stability, thereby making the electrochemical device have good safety performance.

[0009] In one embodiment of the present application, the positive electrode active material includes a lithium transition metal composite oxide, the lithium transition metal composite oxide includes a doping element M, the doping element M includes at least one of Al, Mg, Ti, Cr, Cu, Fe, Co, W, Zn, Ga, Zr, Ru, Ag, Sn, Au, La, Ce, Pr, Nd, Sm, Nb or Gd; the lithium transition metal composite oxide also includes Mn. The selection of the above doping elements is more conducive to improving the cycle performance and rate performance of the electrochemical device.

[0010] Furthermore, the molar ratio of the doping element M to Mn is n M / n Mn is from 0.1% to 10%. For example, the molar ratio n of the doping element M to Mn M / n Mn can be 0.1%, 2%, 4%, 6%, 9%, 10% or any value between any two of the above numerical ranges. Without being limited to any theory, controlling the molar ratio n of the doping element M to Mn M / n Mn within the above range is more beneficial to improving the cycling performance and rate performance of the electrochemical device.

[0011] Further, the positive electrode active material includes Li x Mn y M z O4, where 0.6 ≤ x ≤ 1.2, 0.8 ≤ y ≤ 1, 0 < z ≤ 0.2, and M includes at least one of Al, Mg, Ti, Cr, Cu, Fe, Co, W, Zn, Ga, Zr, Ru, Ag, Sn, Au, La, Ce, Pr, Nd, Sm, Nb, or Gd.

[0012] Preferably, the positive electrode active material includes LiMn 1.96 Al 0.04 O4, LiMn 1.96 Mg 0.04 O4, LiMn 1.92 Al 0.04 Mg 0.04 O4, LiMn 1.88 Al 0.04 Mg 0.04 Nb 0.04 O4, LiMn 1.88 Al 0.08 Nb 0.04 O4, LiMn 1.84 Al 0.12 Nb 0.04 O4, LiMn 1.84 Al 0.16 O4 or LiMn 1.88 Al 0.08 Nb 0.04 O4, etc.

[0013] In an embodiment of the present application, the doping element M includes at least one of Al or Nb. By adding the above doping element M to the positive electrode active material, the cycling performance and rate performance of the electrochemical device are better.

[0014] Further, the molar ratio n of the sum of the molar amounts of Al and Nb to Mn (Al+Nb) / n Mn is from 1% to 10%. For example, the molar ratio n of the sum of the molar amounts of Al and Nb to Mn(Al+Nb) / n Mn It can be 1%, 2%, 4%, 6%, 9%, 10% or any value between any two of the above ranges. Without being limited to any theory, the molar ratio of the sum of the molar amounts of Al and Nb to the molar ratio of Mn is n. (Al+Nb) / n Mn Controlling within the above range is more conducive to improving the cycle performance and rate performance of the electrochemical device.

[0015] In one embodiment of the present application, the positive electrode active material includes secondary particles aggregated from primary particles, wherein the average particle size Ds of the primary particles is 0.8 μm to 5 μm. For example, the average particle size Ds of the primary particles can be 0.8 μm, 1.2 μm, 2.4 μm, 4.3 μm, 5 μm, or any value between any two of the above numerical ranges. Not limited to any theory, if the average particle size Ds of the primary particles is too small, there will be too many active sites, resulting in an increase in side reactions that affect the performance of the electrochemical device; if the average particle size Ds of the primary particles is too large, the contact between the positive electrode active material and the electrolyte is limited, which will affect the performance of the electrochemical device. Controlling the average particle size Ds of the primary particles of the positive electrode active material within the above range is more conducive to improving the cycle performance and rate performance of the electrochemical device.

[0016] In one embodiment of the present application, the average particle size Dv50 of the positive electrode active material is 5 μm to 15 μm. For example, the average particle size Dv50 of the positive electrode active material can be 5 μm, 6.9 μm, 8.4 μm, 8.7 μm, 10.3 μm, 12.4 μm, 12.6 μm, or any value between any two of the above numerical ranges.

[0017] In one embodiment of the present application, the ratio Dv50 / Ds of the average particle size Dv50 of the positive electrode active material to the average particle size Ds of the primary particles is 1.5 to 20. For example, the ratio Dv50 / Ds of the average particle size Dv50 of the positive electrode active material to the average particle size Ds of the primary particles can be 1.5, 1.6, 3.6, 8.6, 10.5, 15.4, 15.5 or any value between any two of the above numerical ranges.

[0018] In one embodiment of the present application, the positive electrode active material is a spinel structure, and the unit cell parameter a of the positive electrode active material is 0.8200nm to 0.8250nm. For example, the unit cell parameter a of the positive electrode active material can be 0.8200nm, 0.8204nm, 0.8214nm, 0.8217nm, 0.8220nm, 0.8226nm, 0.8227nm, 0.8232nm, 0.8233nm, 0.8234nm, 0.8239nm, 0.8250nm or any value between any two of the above numerical ranges. Without being limited to any theory, controlling the unit cell parameter a of the positive electrode active material within the above range is more conducive to the performance of capacity and more conducive to improving the cycle performance and rate performance of the electrochemical device.

[0019] In one embodiment of the present application, the electrochemical device further comprises an electrolyte, and the electrolyte comprises an unsaturated carbonate compound. By adding the unsaturated carbonate compound to the electrolyte, a stable solid electrolyte interface (SEI) film can be formed on the surface of the negative electrode, thereby improving the Mn dissolution of the positive electrode active material, thereby improving the cycle performance of the electrochemical device.

[0020] In one embodiment of the present application, the unsaturated carbonate compound comprises a compound represented by formula (I):

[0021]

[0022] In formula (I), R 3 is selected from substituted C1-C6 alkylene, substituted or unsubstituted C2-C6 alkenylene, when substituted, the substituent comprises at least one of a halogen atom, a C1-C6 alkyl group, and a C2-C6 alkenyl group, and when R 3 When selected from substituted C1-C6 alkylene groups, the substituents include at least C2-C6 alkenyl groups.

[0023] Preferably, the unsaturated carbonate compound is selected from at least one of the following compounds (I-1) to (I-8):

[0024]

[0025] In one embodiment of the present application, based on the mass of the electrolyte, the mass percentage of the unsaturated carbonate compound is 0.01% to 5%. For example, the mass percentage of the unsaturated carbonate compound can be 0.01%, 0.05%, 1%, 2%, 3%, 4%, 5% or any value between any two of the above numerical ranges. Not limited to any theory, if the mass percentage of the unsaturated carbonate compound is too little, its effect of forming a SEI film at the negative electrode to improve the cycle performance of the electrochemical device is not obvious; if the mass percentage of the unsaturated carbonate compound is too high, the SEI film formed at the negative electrode is too thick, which will lead to increased impedance and reduced rate performance. Therefore, controlling the mass percentage of the unsaturated carbonate compound within the above range is more conducive to improving the cycle performance and rate performance of the electrochemical device.

[0026] The electrolyte of the present application also includes lithium salts and non-aqueous solvents. The present application does not particularly limit the type of lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include at least one of lithium hexafluorophosphate (LiPF6), LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3 or LiSiF6. Preferably, LiPF6 may be included because LiPF6 can give high ionic conductivity and improve the cycle performance of lithium-ion batteries. The present application does not particularly limit the non-aqueous solvent, as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include at least one of a carbonate compound, a carboxylate compound, an ether compound or other organic solvents. The above-mentioned carbonate compound may be at least one of a chain carbonate compound or a cyclic carbonate compound. The above-mentioned chain carbonate compound may include at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). Cyclic carbonate compounds can include at least one of ethylene carbonate (EC), propylene carbonate (PC) or butylene carbonate (BC). The above-mentioned carboxylate compounds can include at least one of ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate or propyl propionate. The above-mentioned ether compounds can include at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents can include at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazole ketone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or phosphoric acid ester.

[0027] The positive electrode sheet of the present application is not particularly limited as long as the object of the present application can be achieved. For example, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer. The positive electrode current collector of the present application is not particularly limited as long as the object of the present application can be achieved. For example, the positive electrode current collector may include aluminum foil, aluminum alloy foil, or composite current collector, etc. The positive electrode material layer of the present application includes the positive electrode active material of any one of the foregoing solutions of the present application. In the present application, the thicknesses of the positive electrode current collector and the positive electrode material layer are not particularly limited as long as the object of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, preferably 6 μm to 18 μm. The thickness of the single-sided positive electrode material layer is 30 μm to 120 μm. In the present application, the positive electrode material layer may be disposed on one surface in the thickness direction of the positive electrode current collector, or may be disposed on both surfaces in the thickness direction of the positive electrode current collector. It should be noted that the "surface" here may be the entire area of the positive electrode current collector or a partial area of the positive electrode current collector, and the present application is not particularly limited as long as the object of the present application can be achieved. Optionally, the positive electrode sheet may further include a conductive layer, and the conductive layer is located between the positive electrode current collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited and may be a commonly used conductive layer in the art. For example, the conductive layer includes a conductive agent and a binder.

[0028] The electrochemical device of the present application further includes a negative electrode sheet. The negative electrode sheet of the present application is not particularly limited as long as the object of the present application can be achieved. For example, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer. The negative electrode current collector of the present application is not particularly limited as long as the object of the present application can be achieved. For example, the negative electrode current collector may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or composite current collector, etc. The negative electrode material layer of the present application includes a negative electrode active material. The type of the negative electrode active material of the present application is not particularly limited as long as the object of the present application can be achieved. For example, the negative electrode active material may include natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO x (0 < x < 2), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel-structured lithium titanate Li4Ti5O 12, Li-Al alloy or at least one of metallic lithium. In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 6μm to 10μm, and the thickness of the single-sided negative electrode material layer is 30μm to 130μm. In the present application, the negative electrode material layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. There is no particular restriction in the present application, as long as the purpose of the present application can be achieved. Optionally, the negative electrode sheet may also include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The composition of the conductive layer is not particularly limited, and it may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder.

[0029] The above-mentioned conductive agent is not particularly limited, as long as the purpose of the application can be achieved. For example, the conductive agent may include at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon nanofibers, graphite, acetylene black, carbon black, Ketjen black, carbon dots or graphene. For example, the binder may include at least one of polypropylene alcohol, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyimide, polyamide-imide, styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), polyvinylidene fluoride, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), water-based acrylic resin, carboxymethyl cellulose (CMC) or sodium carboxymethyl cellulose (CMC-Na).

[0030] The electrochemical device of the present application also includes a diaphragm to separate the positive electrode plate and the negative electrode plate, prevent the internal short circuit of the lithium-ion battery, allow the electrolyte ions to pass freely, and complete the electrochemical charge and discharge process. The diaphragm in the present application is not particularly limited, as long as the purpose of the present application can be achieved. For example, a polyolefin (PO) diaphragm mainly composed of polyethylene (PE) and polypropylene (PP), a polyester film (such as polyethylene terephthalate (PET) film), a cellulose film, a polyimide film (PI), a polyamide film (PA), spandex, an aramid film, a woven film, a non-woven film (non-woven fabric), a microporous film, a composite film, a diaphragm paper, a rolled film, and a spinning film. At least one. For example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer can be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the inorganic particles are not particularly limited, for example, they can be selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The binder is not particularly limited, for example, it can be selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The polymer layer contains polymers, and the polymer material includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).

[0031] The electrochemical device of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In some embodiments, the electrochemical device may include, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery, or a lithium ion polymer secondary battery.

[0032] The preparation process of the electrochemical device is well known to those skilled in the art, and the present application has no particular limitation. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a wound structure, placing the electrode assembly in a packaging shell, injecting an electrolyte into the packaging shell and sealing it to obtain an electrochemical device; or stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging shell, injecting an electrolyte into the packaging shell and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the packaging shell as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.

[0033] The second aspect of the present application provides an electrical device, comprising the electrochemical device described in any of the above embodiments. The electrical device has good cycle performance, rate performance and safety performance.

[0034] The electrical equipment of the present application is not particularly limited, and may include but is not limited to the following types: laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.

[0035] The present application provides an electrochemical device and an electrical equipment including the electrochemical device, wherein the electrochemical device includes a positive electrode sheet, the positive electrode sheet includes a positive electrode active material, and when the state of charge SOC of the electrochemical device is 90% to 100%, the DSC curve of the positive electrode sheet has a first exothermic peak A1 and a second exothermic peak A2 between 150°C and 400°C, wherein, based on the mass of the positive electrode active material, the first exothermic peak A1 is an exothermic peak with a peak intensity greater than 0.1mW / mg closest to 400°C, the second exothermic peak A2 is an exothermic peak with a peak intensity greater than 0.1mW / mg closest to 150°C, and the difference between the peak position Ta of the first exothermic peak A1 and the peak position Tb of the second exothermic peak A2 is 20°C to 150°C. The electrochemical device has good cycle performance, rate performance and safety performance. The electronic device including the electrochemical device also has good cycle performance, rate performance and safety performance. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme, and advantages of the present application more clearly understood, the present application is further described in detail with reference to the embodiments below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other technical schemes obtained by ordinary technicians in the field belong to the scope of protection of the present application.

[0037] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.

[0038] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0039] Test methods and equipment:

[0040] DSC Test:

[0041] DSC is used to measure the relationship between the heat flow difference and temperature of the sample and the reference. The DSC curve was tested using a STA449F3 model synchronous thermal analyzer. The method is as follows: the lithium-ion battery was charged to 100% SOC, disassembled, the positive electrode was taken out, and cut into 10cm×10cm specifications. The test temperature range was 150℃ to 400℃, and the heating rate was 10℃ / min to obtain the DSC curve.

[0042] Test of the content of each element in the positive electrode active material:

[0043] Discharge the lithium-ion battery to 2.8V, disassemble it, take out the positive electrode sheet, wash it with high-purity anhydrous DMC for 3 times, soak it for 8 hours each time, and then let it stand in a vacuum drying oven for 12 hours. Scrape the positive active material from the positive electrode sheet and perform an inductively coupled plasma spectrometer (ICP) test.

[0044] Test of average particle size Ds of primary particles:

[0045] The average particle size Ds of the primary particles of the positive electrode active material was tested by scanning electron microscopy. After the positive electrode material was imaged by scanning electron microscopy (German ZEISS Sigma-02-33), 200 primary particles of the positive electrode active material with complete shape and no obstructions were randomly selected from the electron microscopic image, and the average value of the longest diameter of the primary particles in the microscopic image was recorded as the average particle size Ds.

[0046] Test of average particle size Dv50:

[0047] Tested by Mastersizer 3000 laser particle size distribution tester. Laser particle size test is based on the principle that particles of different sizes can cause laser to scatter with different intensities to test particle size distribution. Dv50 represents the particle size that reaches 50% of the volume accumulation from the small particle size side in the volume-based particle size distribution.

[0048] Calculation of injection coefficient:

[0049] Filling coefficient = electrolyte capacity / lithium-ion battery capacity.

[0050] High temperature capacity retention test:

[0051] At 45°C, charge the lithium-ion battery to 4.2V at a constant current of 0.5C, and finally charge it at a constant voltage until the current reaches 0.05C, and record the charging capacity of the first cycle; then discharge it to 3.0V at a constant current of 1C, and record the discharge capacity of the first cycle. Then, perform 500 charge and discharge cycles in the same steps, and record the discharge capacity of the 500th cycle. The capacity retention rate is used as an indicator to evaluate the cycle performance of lithium-ion batteries.

[0052] Capacity retention rate = (discharge capacity at the 500th cycle / first discharge capacity) × 100%.

[0053] Rate performance test:

[0054] At 25°C, the lithium-ion secondary battery was charged to 4.2V at a constant current of 0.2C, then charged to 0.05C at a constant voltage, left to stand for 30 minutes, and then discharged to 3.0V at a constant current of 0.2C. The discharge capacity of the lithium-ion battery at 0.2C rate was obtained by testing.

[0055] At 25°C, the lithium-ion secondary battery was charged at a constant current of 0.2C to 4.2V, then charged at a constant voltage to a current less than or equal to 0.05C, then left to stand for 30 minutes, and then discharged at a constant current of 1C to 3.0V. The 1C rate discharge capacity of the lithium-ion secondary battery was obtained by testing.

[0056] Lithium-ion battery 1C rate discharge capacity retention rate (%) = 1C rate discharge capacity / 0.2C rate discharge capacity × 100%.

[0057] Example 1-1

[0058] <Preparation of positive electrode sheet>

[0059] The positive electrode active material LiMn 1.96 Al 0.04O4, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 96:2:2, and NMP is added as a solvent to prepare a slurry with a solid content of 75%, and stirred under the action of a vacuum mixer until the system becomes a uniform positive electrode slurry. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10 μm, and dried at 90°C to obtain a positive electrode sheet with a single-sided coating of positive electrode material with a coating thickness of 110 μm. After that, the above steps are repeated on the other surface of the positive electrode sheet to obtain a positive electrode sheet with a double-sided coating of positive electrode material. After coating, the positive electrode sheet is cut into a size of 74 mm × 867 mm for standby use. Among them, the Ds of the positive active material is 0.8 μm, the Dv50 is 12.4 μm, and the unit cell parameter a of the positive active material is 0.8220 nm.

[0060] <Preparation of negative electrode sheet>

[0061] The negative electrode active material graphite, binder SBR, and thickener sodium carboxymethyl cellulose are mixed in a weight ratio of 97.5:1.5:1, and then deionized water is added as a solvent to prepare a negative electrode slurry with a solid content of 70%, and stirred under the action of a vacuum mixer until the system becomes a uniform negative electrode slurry. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 8μm, and dried at 90°C to obtain a negative electrode sheet with a single-sided coating of negative electrode material with a coating thickness of 130μm. After that, the above steps are repeated on the other surface of the negative electrode to obtain a negative electrode sheet with a double-sided coating of negative electrode material. After the coating is completed, the negative electrode sheet is cut into a specification of 76mm×851mm for standby use.

[0062] <Preparation of Separator>

[0063] A diaphragm with a polyethylene porous substrate coated with a ceramic coating on both sides is selected.

[0064] <Preparation of Electrolyte>

[0065] In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate EC, diethyl carbonate DEC, propylene carbonate PC, and propyl propionate PP are uniformly mixed in a mass ratio of 20:30:20:30 to obtain an organic solvent. Vinylene carbonate (VC) and lithium salt LiPF6 are added to the organic solvent and mixed uniformly to obtain an electrolyte. Among them, the concentration of LiPF6 is 1.15 mol / L, and the mass percentage of VC based on the mass of the electrolyte is 0.05%.

[0066] <Preparation of lithium-ion batteries>

[0067] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging shell, placed in a vacuum oven at 85°C for 12 hours to remove moisture, and the prepared electrolyte is injected. After vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained. Among them, the injection coefficient is 4.55g / Ah, the upper limit voltage of the formation after packaging is 4.12V, the formation temperature is 85°C, and the formation standing time is 2.3h.

[0068] In Example 1-2, except that the mass percentage of VC based on the mass of the electrolyte in <Preparation of Electrolyte> is 1%, and the upper limit voltage of formation after packaging in <Preparation of Lithium-ion Battery> is 4.15V, the formation temperature is 88°C, and the formation standing time is 2.7h, the rest is the same as Example 1-1.

[0069] In Example 1-3, except that the upper limit voltage after packaging in <Preparation of Lithium Ion Battery> is 4.18 V, the formation temperature is 90° C., and the formation standing time is 3.0 h, the rest is the same as Example 1-2.

[0070] In Example 1-4, except that the upper limit voltage after packaging in <Preparation of Lithium Ion Battery> is 4.21 V, the formation temperature is 93° C., and the formation standing time is 3.4 h, the rest is the same as Example 1-2.

[0071] In Example 1-5, except that the mass percentage of VC based on the mass of the electrolyte in <Preparation of Electrolyte> is 5% and the injection coefficient in <Preparation of Lithium-ion Battery> is 4.35 g / Ah, the rest is the same as Example 1-1.

[0072] In Example 1-6, except that the mass percentage of VC based on the mass of the electrolyte in <Preparation of Electrolyte> is 3%, and the injection coefficient in <Preparation of Lithium-ion Battery> is 4.15 g / Ah, the rest is the same as Example 1-1.

[0073] In Examples 2-1 to 2-12, except that the mass percentage of VC is 1% based on the mass of the electrolyte in <Preparation of Electrolyte>, the type of positive electrode active material, n M / n Mn 、n (Al+Nb) / n Mn , except for the unit cell parameter a, the rest is the same as Example 1-1.

[0074] In Example 3-1 to Example 3-7, except for adjusting Ds, Dv50, Dv50 / Ds, and unit cell parameter a according to Table 3, the rest is the same as Example 2-4.

[0075] In Example 4-1, except that the positive electrode active material in <Preparation of positive electrode sheet> is LiMn 1.88 Al 0.08 Nb 0.04 O4, Ds is 2.4μm, Dv50 is 8.7μm, the unit cell parameter a is 0.8232nm, 4,5-dimethyl-1,3-dioxol-2-one (DMDO) (I-6) is used instead of VC in <Preparation of electrolyte>, and the mass percentage of 4.5-dimethyl-1,3-dioxol is 1% based on the mass of the electrolyte, and the filling coefficient in <Preparation of lithium-ion battery> is 4.53g / Ah, the upper limit voltage of formation after packaging is 4.13V, the formation temperature is 86°C, and the formation standing time is 2.3h, the rest is the same as Example 1-1.

[0076] In Example 4-2, except that a combination of 4.5-dimethyl-1,3-dioxol and VC is used in <Preparation of Electrolyte>, and based on the mass of the electrolyte, the mass percentage of 4,5-dimethyl-1,3-dioxol-2-one (DMDO) is 1%, and the mass percentage of VC is 1%, in <Preparation of Lithium-ion Battery>, the injection coefficient is 4.57 g / Ah, the upper limit voltage of formation after packaging is 4.15 V, the formation temperature is 88°C, and the formation standing time is 2.3 h, the rest is the same as Example 4-1.

[0077] In Example 4-3, except that the positive electrode active material in <Preparation of positive electrode sheet> is LiMn 1.84 Al 0.16 O4, Ds is 2.4μm, Dv50 is 8.7μm, the cell parameter a is 0.8214nm, the mass percentage of VC based on the mass of the electrolyte in <Preparation of Electrolyte> is 2%, the filling coefficient in <Preparation of Lithium-ion Battery> is 4.6g / Ah, the upper limit voltage of formation after packaging is 4.2V, the formation temperature is 88°C, and the formation standing time is 2.5h, the rest is the same as Example 1-1.

[0078] In Example 4-4, except that the mass percentage of VC based on the mass of the electrolyte in <Preparation of Electrolyte> is 4%, the rest is the same as Example 4-3.

[0079] In Comparative Example 1, except that the mass percentage of VC based on the mass of the electrolyte in <Preparation of Electrolyte> is 4%, the filling coefficient in <Preparation of Lithium-ion Battery> is 4.06 g / Ah, the upper limit voltage of formation after packaging is 4.20 V, and the formation temperature is 88°C, the rest is the same as Example 1-1.

[0080] The relevant preparation parameters and performance parameters of Examples 1-1 to 1-6 and Comparative Example 1 are shown in Table 1, the relevant preparation parameters and performance parameters of Examples 2-1 to 2-12 are shown in Table 2, the relevant preparation parameters and performance parameters of Examples 3-1 to 3-7 are shown in Table 3, and the relevant preparation parameters and performance parameters of Examples 4-1 to 4-4 are shown in Table 4:

[0081] Table 1

[0082]

[0083] It can be seen from Examples 1-1 to 1-6 and Comparative Example 1 that the rate performance and cycle performance (capacity retention rate) of the lithium ion battery change with the peak position Ta and peak intensity of the first exothermic peak A1, and the peak position Tb and peak intensity of the second exothermic peak A2. The lithium ion battery in which the peak intensity of the second exothermic peak A2 is greater than 0.1 mW / mg, and the difference between the peak position Ta of the first exothermic peak A1 and the peak position Tb of the second exothermic peak A2 is within the scope of the present application, has better rate performance and cycle performance.

[0084]

[0085]

[0086]

[0087]

[0088] By comparing Examples 2-1 to 2-12, it can be seen that compared with Example 2-1 doped with only Mg, Examples 2-2 to 2-12 doped with Al and / or Nb can significantly improve the cycle performance of lithium-ion batteries, and as long as the type of positive electrode active material and the molar ratio of the doping element M to Mn are M / n Mn , the molar ratio of the sum of the molar amounts of Al and Nb to Mn (Al+Nb) / n Mn , the unit cell parameter a of the positive electrode active material is within the scope of this application, and the lithium-ion battery can have good rate performance and cycle performance.

[0089] It can be seen from Example 3-1 to Example 3-7 that the embodiments in which the average particle size Ds of the primary particles of the positive electrode active material is in the range of 0.8μm to 5μm, the average particle size Dv50 of the positive electrode active material is in the range of 5μm to 15μm, and Dv50 / Ds is in the range of 1.5 to 20 can simultaneously have excellent rate performance and cycle performance.

[0090] It can be seen from Example 4-1 to Example 4-4 that by selecting different types of unsaturated carbonate compounds and their contents, and by regulating the injection coefficient and formation conditions, lithium-ion batteries can have good rate performance and cycle performance.

[0091] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. An electrochemical device comprising a positive electrode sheet and an electrolyte, wherein the positive electrode sheet comprises a positive electrode active material; When the state of charge (SOC) of the electrochemical device is 90% to 100%, the DSC curve of the positive electrode sheet has a first exothermic peak A1 and a second exothermic peak A2 between 150° C. and 400° C., wherein: Based on the mass of the positive electrode active material, the first exothermic peak A1 is an exothermic peak with a peak intensity greater than 0.1 mW / mg closest to 400° C., the second exothermic peak A2 is an exothermic peak with a peak intensity greater than 0.1 mW / mg closest to 150° C., the difference between the peak position Ta of the first exothermic peak A1 and the peak position Tb of the second exothermic peak A2 is 20° C. to 150° C., The positive electrode active material includes a spinel-structured lithium transition metal composite oxide, the lithium transition metal composite oxide includes a doping element M, and the doping element M includes at least one of Al, Mg, Ti, Cr, Cu, Fe, Co, W, Zn, Ga, Zr, Ru, Ag, Sn, Au, La, Ce, Pr, Nd, Sm, Nb or Gd; The lithium transition metal composite oxide further comprises Mn, and the molar ratio of the doping element M to Mn is n M / n Mn 0.1% to 10%; and The electrolyte includes unsaturated carbonate compounds.

2. The electrochemical device according to claim 1, wherein: The peak position Ta of the first exothermic peak A1 is located at 250°C to 400°C, and the peak position Tb of the second exothermic peak A2 is located at 200°C to 300°C.

3. The electrochemical device according to claim 1, wherein The ratio S of the peak intensity of the first exothermic peak A1 to the peak intensity of the second exothermic peak A2 is 0.1 to 10.

4. The electrochemical device according to claim 1, wherein After soaking the positive electrode plate in N-methylpyrrolidone at 25°C for 8h, the N-methylpyrrolidone was replaced and the soaking was repeated twice. The DSC curve of the positive electrode plate had an exothermic peak B between 240°C and 400°C, and based on the mass of the positive electrode active material, the peak area of ​​the exothermic peak B was less than 360J / g.

5. The electrochemical device according to claim 1, wherein The doping element M includes at least one of Al and Nb, wherein the molar ratio of the sum of the molar amounts of Al and Nb to the molar amount of Mn is n (Al+Nb) / n Mn It is between 1% and 10%.

6. The electrochemical device according to claim 1, wherein The positive electrode active material includes secondary particles formed by aggregation of primary particles, and the electrochemical device satisfies at least one of the following conditions a) to d): a) the average particle size Ds of the primary particles is 0.8 μm to 5 μm; b) the average particle size Dv50 of the positive electrode active material is 5 μm to 15 μm; c) the ratio Dv50 / Ds of the average particle size Dv50 of the positive electrode active material to the average particle size Ds of the primary particles is 1.5 to 20; d) The unit cell parameter a of the positive electrode active material is 0.8200 nm to 0.8250 nm.

7. The electrochemical device according to claim 1, wherein: The unsaturated carbonate compound comprises a compound represented by formula (I), In formula (I), R 3 is selected from substituted C1-C6 alkylene, substituted or unsubstituted C2-C6 alkenylene, when substituted, the substituent comprises at least one of a halogen atom, a C1-C6 alkyl group, a C2-C6 alkenyl group, and when R 3 When selected from substituted C1-C6 alkylene groups, the substituents include at least C2-C6 alkenyl groups.

8. The electrochemical device according to claim 7, wherein: The unsaturated carbonate compound is selected from at least one of the following compounds (I-1) to (I-8):

9. The electrochemical device according to claim 1, wherein: Based on the mass of the electrolyte, the mass percentage of the unsaturated carbonate compound is 0.01% to 5%.

10. An electrical equipment comprising the electrochemical device according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Doped modified lithium nickel cobalt manganese material, preparation method thereof and lithium ion battery

    CN103296249A

  • Electrochemical device and electronic device including same

    CN111416152A